MODERNISASI POS LINTAS BATAS NEGARA ENTIKONG DAN DAMPAKNYA TERHADAP AKTIVITAS EKONOMI LINTAS BATAS INDONESIA–MALAYSIA - Destian Khaldiansyah Rauf; Candra Yusuf; Mohamad Ikbal Kadir (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2026)
order areas play a strategic role as gateways to national sovereignty and regional economic integration. The modernization of Indonesia's Border Crossing Posts (Pos Lintas Batas Negara/PLBN) has become one of the government's priority policies to strengthen connectivity, improve public services, and stimulate economic growth in border regions. However, previous studies have predominantly examined PLBN modernization from the perspectives of infrastructure development and border security, while limited attention has been given to its implications for cross-border economic activities. This study aims to analyze the modernization process of the Entikong Border Crossing Post (PLBN) and examine its impact on cross-border economic activities between Indonesia and Malaysia. A qualitative descriptive approach was employed using secondary data obtained from scientific literature, government reports, policy documents, and other relevant publications. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña to identify the relationship between infrastructure transformation and regional economic dynamics. The findings indicate that the modernization of PLBN Entikong has significantly improved infrastructure quality, service efficiency, and regional connectivity, resulting in smoother cross-border mobility of goods and people. The modernization has also encouraged the formalization of economic activities, strengthened the development of micro, small, and medium enterprises (MSMEs), increased trade activities, and created broader investment opportunities. Nevertheless, greater market openness has intensified competition between local products and imported goods from neighboring Malaysia. The study concludes that the modernization of PLBN Entikong constitutes a strategic instrument for strengthening regional economic integration, enhancing the competitiveness of border areas, and promoting sustainable local economic development while reinforcing Indonesia's border governance.